(Re-)telling Newfoundland Sealing Masculinity: Narrative and Counter-narrative - Keough, Willeen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2010)
Throughout the controversy over Newfoundland sealing in the latter twentieth century, anti-sealing protest and counter-protest movements, government policy, the media, and the broader arena of international opinion all became sites for the creation of knowledge about Newfoundland sealing masculinity. Sealers engaged with these various discourses as they negotiated their own masculine identities. Recent interviews with sealers of the period reveal the complexity of this process. Not surprisingly, they challenged negative portrayals by their environmentalist critics. More intriguingly, they often positioned themselves outside a Newfoundland cultural narrative of “jolly ice-hunters” and undaunted heroes of the ice- floes. This article explores the disconnect between a romanticized, static cultural understanding of sealing masculinity and the more grounded, nuanced masculinity articulated by sealers and their local communities.